THE DIDACTIC CONTRACT AND ITS HORIZON OF EXPECTATION - Thomas Hausberger, Thomas; Patras, Frédéric (Educere et Educare, 2020)
The aim of the present article is to investigate the meaning of the didactic contract from the point of view of a key philosophical concept, originated in Husserl’s phenomenology, namely the notion of horizon. We feature in particular the notion of horizon of expectation, as developed by H. R. Jauss and the Constance School. The core of the article is to explicit the ideas that result from the confrontation of the principles governing the notion of didactic contract with the idea of horizon of expectation. This theoretical perspective is illustrated with two case studies: the dialog between two graduate students who are working on a mathematical problem that has been elaborated with the methodology of didactic engineering and an oral communication between professional mathematicians in the context of a research seminar in mathematics. We conclude by reflexive comments about the nature of interactions between the fields of philosophy and mathematics education and lastly comment on the fertility of networking approaches from didactics of mathematics and hermeneutics. Namely, we underline that hermeneutics and phenomenology may be applied in the context of mathematics education but also, conversely, that didactical contexts and theoretical constructs may enrich philosophical accounts.